Sex-related differences among patients undergoing surgical aortic valve replacement—a propensity score matched study - Zierer, Andreas; De Paulis, Ruggero; Bakhtiary, Farhad; Ahmad, Ali El Sayed; Andreas, Martin; Autschbach, Rüdiger; Benedikt, Peter; Binder, Konrad; Bonaros, Nikolaos; Borger, Michael; Bourguignon, Thierry; Canovas, Sergio; et al. (Interdisciplinary CardioVascular and Thoracic Surgery, 2024)
OBJECTIVES: We investigated the sex-related difference in characteristics and 2-year outcomes after surgical aortic valve replacement (SAVR) by propensity-score matching (PSM). METHODS: Data from 2 prospective registries, the INSPIRIS RESILIA Durability Registry (INDURE) and IMPACT, were merged, resulting in a total of 933 patients: 735 males and 253 females undergoing first-time SAVR. The PSM was performed to assess the impact of sex on the SAVR outcomes, yielding 433 males and 243 females with comparable baseline characteristics. RESULTS: Females had a lower body mass index (median 27.1 vs 28.0 kg/m2; P ¼ 0.008), fewer bicuspid valves (52% vs 59%; P ¼ 0.036), higher EuroSCORE II (mean 2.3 vs 1.8%; P < 0.001) and Society of Thoracic Surgeons score (mean 1.6 vs 0.9%; P < 0.001), were more often in New York Heart Association functional class III/IV (47% vs 30%; P < 0.001) and angina Canadian Cardiovascular Society III/IV (8.2% vs 4.4%; P < 0.001), but had a lower rate of myocardial infarction (1.9% vs 5.2%; P ¼ 0.028) compared to males. These differences vanished after PSM, except for the EuroSCORE II and Society of Thoracic Surgeons scores, which were still significantly higher in females. Furthermore, females required smaller valves (median diameter 23.0 vs 25.0 mm, P < 0.001). There were no differences in the length of hospital stay (median 8 days) or intensive care unit stay (median 24 vs 25 hours) between the 2 sexes. At 2 years, post-SAVR outcomes were comparable between males and females, even after PSM. CONCLUSIONS: Despite females presenting with a significantly higher surgical risk profile, 2-year outcomes following SAVR were comparable between males and females.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Aortic stenosis; Sex disparities; Surgical aortic valve replacement